Potential lost productivity resulting from the global burden of uncorrected refractive error - TST Smith; KD Frick; BA Holden; TR Fricke; KS Naidoo (The World Health Organization, 2009)
OBJECTIVE: To estimate the potential global economic productivity loss associated with the existing burden of visual impairment from uncorrected refractive error (URE). METHODS: Conservative assumptions and national population, epidemiological and economic data were used to estimate the purchasing power parity-adjusted gross domestic product (PPP-adjusted GDP) loss for all individuals with impaired vision and blindness, and for individuals with normal sight who provide them with informal care. FINDINGS: An estimated 158.1 million cases of visual impairment resulted from uncorrected or undercorrected refractive error in 2007; of these, 8.7 million were blind. We estimated the global economic productivity loss in international dollars (I$) associated with this burden at I$ 427.7 billion before, and I$ 268.8 billion after, adjustment for country-specific labour force participation and employment rates. With the same adjustment, but assuming no economic productivity for individuals aged > 50 years, we estimated the potential productivity loss at I$ 121.4 billion. CONCLUSION: Even under the most conservative assumptions, the total estimated productivity loss, in $I, associated with visual impairment from URE is approximately a thousand times greater than the global number of cases. The cost of scaling up existing refractive services to meet this burden is unknown, but if each affected individual were to be provided with appropriate eyeglasses for less than I$ 1000, a net economic gain may be attainable.